Identification of aerodynamic admittance functions of a flat closed-box deck in different grid-generated turbulent wind fields. Issue 3 (February 2018) - Yan, Lei; Zhu, Le-Dong; Flay, Richard George James
Wind tunnel tests of synchronous measurements of the buffeting lifts and moments on six separated strips of a motionless 1:45 scale sectional model of a flat closed-box bridge deck were carried out in three turbulent flow conditions. The longitudinal and vertical components of turbulent wind speed were also measured synchronously with the buffeting forces at the positions just over the windward edges of the six strips. Three typical methods, including the auto-spectral method based on the measured auto-spectrum of buffeting force (auto-spectrum method), the cross-spectral method based on the measured cross-spectra between buffeting force and fluctuating turbulence components (cross-spectrum method), and the colligated least square method based on a colligated residue of the above-mentioned auto- and cross-spectra (colligated least square method), were then used, respectively, to identify the aerodynamic admittance functions of the flat closed-box deck. The aerodynamic admittance function components of a buffeting force with respect to the longitudinal and vertical components of fluctuating wind speed were effectively separated using the colligated least square method while only a weighted average value, often called the equivalent aerodynamic admittance function, was obtained using the auto-spectrum method. Meanwhile, the reproduced auto-spectra of the buffeting forces had very high accuracies when the aerodynamic admittance functions identified with the colligated least square method were employed, but deviated significantly from the measured ones when the aerodynamic admittance functions identified with the cross-spectrum method were used. Furthermore, the influence of the span-wise position of the wind probe on the values of aerodynamic admittance function module was confirmed to be very small. Finally, the aerodynamic admittance function components with respect to the longitudinal and vertical fluctuating wind speeds were found to be significantly affected by both the intensities and integral scales of the oncoming turbulence wind.